The evolution of sprinting performance: Technological and regulatory influences from 1976 to 2024 - Skalski, D. T.; Pronczuk, M.; Losinska, K.; Lulinska, E.; Motowidlo, J.; Stastny, P.; Maszczyk, A.; Trybek, G. (Baltic Journal of Health and Physical Activity, 2025)
Background: This study examines the progression of sprinting performance across the 100m, 200m, and 400m events from 1976 to 2024, highlighting the influence of technological advancements and regulatory changes. Over the past decades, sprinting has been significantly shaped by developments in track surfaces, footwear technology, training methodologies, and regulatory frameworks. Understanding these factors is essential for assessing how sprint times have evolved and what future trends might emerge.